Penerapan Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil (Studi Kasus di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Banyumas) - Aji Wirawan, Kresna Anggoro; Amarini, Indriati (UMPurwokerto Law Review, 2024)
Abstract Government Regulation Number 53 of 2010 concerning Civil Servant Discipline which has been replaced by the issuance of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. The Banyumas Regency Personnel and Human Resources Development Agency has recorded 2 (Two) State Civil Apparatus who are threatened with severe sanctions due to disciplinary violations. Government Regulation Number 53 of 2010 concerning Civil Servant Discipline which has been replaced by Government Regulation Number 94 of 2021 concerning civil servant discipline Significant differences exist in the sanctions for moderate and severe violations. This article aims to analyze the settlement for indisciplinary civil servants in doing their work and the factors that become obstacles in the settlement of indisciplinary civil servants in Banyumas Regency. The research method used in this research is normative juridical. Research on the settlement of indiscipline imposed by the Banyumas Regency Personnel and Human Resources Development Agency has been carried out based on Government Regulation Number 94 of 2021 concerning Civil Servant Discipline with evidence that cases of indiscipline violations from 2020 to 2022 can be resolved properly. Factors that become obstacles are due to the lack of supervision and guidance of civil servants on violations of discipline committed by authorized officials, as well as the influence of a bad environment, causing habits of violation of discipline, they consider that these violations can still be tolerated. Keywords: violation, indiscipline, civil servants Abstract Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil yang telah diganti dengan dikeluarkannya Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil. Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Banyumas mencatat 2 (Dua) Aparatur Sipil Negara Yang terancam terkena sanksi berat karena pelanggaran Indisipliner. Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil yang telah diganti Menjadi Peraturan Pemerintah Nomor 94 Tahun 2021 tentang disiplin pegawai negeri sipil Perbedaan yang signifikan terdapat dalam sanksi hukuman pelanggaran tingkat sedang dan tingkat berat. Artikel ini bertujuan untuk menganalisis tentang penyelesaian bagi para Pegawai Negeri Sipil yang indisipliner dalam melakukan pekerjaannya dan Faktor yang menjadi hambatan dalam penyelesaian indisipliner Pegawai Negeri Sipil di Kabupaten Banyumas. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif. Penelitian Penyelesaian Indisipliner yang di jatuhkan Badan Kepegawian dan Pengembangan Sumber Daya Manusia Kabupaten Banyumas telah dilakukan berdasarkan Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil dengan adanya bukti bahwa kasus pelanggaran Indisipliner yang selama tahun 2020 sampai 2022 dapat di selesaikan dengan baik. Faktor yang menjadi hambatan dikarenakan Pegawai Negeri Sipil tersebut kurang dalam pengawasan dan pembinaan terhadap pelanggaran disiplin yang dilakukan oleh Pejabat yang berwenang, serta pengaruh lingkungan yang kurang baik, menimbulkan kebiasaan terjadinya pelanggaran disiplin, mereka menganggap bahwa pelanggaran tersebut masih bisa di tolerir. Keywords: pelanggaran, indisipliner, pegawai negeri sipil